PREVENTION OF TRAFFICKING IN HUMAN BEINGS AT THE NATIONAL AND INTERNATIONAL LEVEL - SANDU, Ionel (International Journal of Legal and Social Order, 2022)
Trafficking in persons has become a category of crimes that increasingly concerns the authorities with powers in the field of combating acts of an antisocial nature, but the shock wave that this type of criminal acts produces is of a much greater amplitude, causing social disturbances, psychological-behavioral, economic including financial, with a harmful impact on the defense system of national and international public order and safety.